Potential of food protein-derived peptides for the improvement of osteoarthritis. (November 2022) - Xiong, Ling; Luo, Tao; Wang, Luanfeng; Weng, Zebin; Song, Haizhao; Wang, Fang; Shen, Xinchun
Abstract: Background: Bioactive peptides from different food protein have been reported to have a lot of biological activities, such as anti-inflammation and anti-oxidation, making them beneficial for chronic disease. Osteoarthritis (OA) is one of the major diseases affecting human health worldwide. The main treatment methods of OA are physiotherapy, medication and surgery. Many drug, such as adrenocortical hormone, have serious side effects on the patients. Therefore, it is necessary to search for treatment with less side effects. Recently, biologically active peptides from natural foods have been extensively reported to show beneficial effects on alleviating symptom of osteoarthritis, which make it potential for industrial application in the functional foods. Scope and approach: In this review, we focus on biological characteristics of food-derived peptides, especially their therapeutic effect in osteoarthritis, and the underlying mechanism by which these peptides exert the biologically function in osteoarthritis. Key findings and conclusions: Peptides from bovine, chicken, deer are the predominant species for improvement of osteoarthritis in in vitro, in vivo and clinical studies. Marine food is another important protein source for production of bioactive peptide that showed beneficial effect in the treatment of osteoarthritis. A few peptides from plant protein such as soybean protein also showed positive effect on chondrocytes. However, many bioactive peptides that showed the beneficial effect on osteoarthritis were in the form of mixture. Finding out the exact peptide that exerts the positive effect in the osteoarthritis is necessary for the industrial application in the future. Graphical abstract: Image 1 Highlights: Food-derived peptides significantly alleviated symptom of osteoarthritis. MAPK and Wnt signaling pathway were involved in the improvement of osteoarthritis mediated by food-derived peptides. Peptides with anti-inflammatory and antioxidant activity had the great potential in the intervention of osteoarthritis.